2023
DOI: 10.1180/mgm.2023.25
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the anthropogenic origin of the ‘Carmel sapphire’ with enigmatic super-reduced minerals

Abstract: Corundum with inclusions of enigmatic super-reduced (SR) minerals was found in mineral separates received as a result of alluvial sediment exploration near Mt Carmel, Israel by the Shefa Yamim Company. This corundum, registered as "Carmel sapphire TM " (CS), has been an object of numerous publications by W. Griffin's scientific team, in which they propose a questionable hypothesis of CS formation at the crust-mantle boundary with the participation of CH4+H2 fluids. Often the CS is in small fragments of breccia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Indeed, there are cases where skeletal osbornite crystals can be found completely inside corundum. In our samples, osbornite is typically confined to glass inclusions (Galuskin and Galuskina, 2023, figs S5D, S6C, supplementary materials).…”
Section: Background Informationmentioning
confidence: 91%
See 4 more Smart Citations
“…Indeed, there are cases where skeletal osbornite crystals can be found completely inside corundum. In our samples, osbornite is typically confined to glass inclusions (Galuskin and Galuskina, 2023, figs S5D, S6C, supplementary materials).…”
Section: Background Informationmentioning
confidence: 91%
“…The investigation of this specific 'white breccia' showed that it is a furnace charge (calcined bauxite) for electrocorundum production mixed with waste from its production. That led us to write a critical paper on the genesis of Carmel sapphire (Galuskin and Galuskina, 2023).…”
Section: Background Informationmentioning
confidence: 99%
See 3 more Smart Citations